ANALISA EFEKTIVITAS ALAT PENUKAR PANAS - Sulaeman; Nofitra Satria (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2014)
Heat Exchanger is a device that is used to transfer heat from one medium to another. At Environment ITP there are many kinds of dryers, but they are still depend on the intensity of sunlight. The Heat exchanger is an alternative to the drying process in rainy season. Base on the direction of fluid flow, heat exchanger is includes a heat exchanger types of cross flow. Then the air entering the dryer chamber does not mix with the smoke produced by burning sawdust on the furnace fuel. Air enters through the input with the of a blower and continue towards the composition of the pipe as a heat transfer, hot air continues to flow towards the output. In this tool comes two heat transfer process of heat transfer is natural convection and forced convection heat transfer. To determine the effectiveness of this tool, is influenced by several variables such as : speed, burnbing time, the mass of sawdust, pipe surface temperature, the temperature of the cold air and out, the temperature of hot air inside and outside.